Direct and indirect effects of global change on mycorrhizal associations of savanna plant communities. Issue 8 (14th June 2021) - Pérez‐Ramos, Ignacio M.; Álvarez‐Méndez, Andrea; Wald, Katharina; Matías, Luis; Hidalgo‐Galvez, María D.; Navarro‐Fernández, Carmen M.
Abstract : Mycorrhizal fungi are key components of whole‐plant adaptive strategies to cope with different abiotic and biotic constraints. Although they are particularly sensitive to different global change drivers, there are still many gaps on the mechanisms underpinning shifts in mycorrhizal associations under different climatic and management scenarios. We carried out a field manipulative experiment of rainfall exclusion and increased temperature aimed to evaluate the impact of forecasted warming and drying on mycorrhizal associations of savanna plant communities subjected to different grazing history. Additionally, we compiled detailed information on the abiotic and biotic environment with the final aim of disentangling the direct and indirect effects of climate change on this widespread mycorrhizal symbiosis. Our results suggest that climate change could induce relevant changes in mycorrhizal associations, primarily promoted by warming, which decreased the abundance of mycorrhizae but induced higher activity of nutrient exchange between the host–plant and the mycosymbiont. Temperature did not only affect this symbiosis in a direct way, but also exerted relevant indirect effects via changes in soil functioning and other root‐colonizing microorganisms such as dark septate endophytes. Grazing history influenced the allocation of fungal structures inside the host‐root, but its effect differed as a function of the climatic treatment. Results from this study suggest that mycorrhizal fungi might become less prevalent in plant communities inhabiting savanna ecosystems under future scenarios of increasing aridity. In agreement with this finding, higher temperatures also promoted the predominance of plants with root traits that favour efficient resource acquisition by themselves without the help of a mycorrhizal partner. Our results provide new insights into the interactive effects of the two main threats facing Mediterranean savanna ecosystems, as well as potentially useful information to be applied in ecologically‐based management strategies aimed at attenuating the potential impact of global change on mycorrhizal fungi.